2016
DOI: 10.3791/53556
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensionally Printed Microfluidic Cross-flow System for Ultrafiltration/Nanofiltration Membrane Performance Testing

Abstract: Minimization and management of membrane fouling is a formidable challenge in diverse industrial processes and other practices that utilize membrane technology. Understanding the fouling process could lead to optimization and higher efficiency of membrane based filtration. Here we show the design and fabrication of an automated three-dimensionally (3-D) printed microfluidic cross-flow filtration system that can test up to 4 membranes in parallel. The microfluidic cells were printed using multi-material photopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…After this treatment, scanning electron microscopy showed that the membrane surface and pores that were previously covered by the photoinitiator coating became visible again (Figure S3). Membrane performance testing utilized a custom designed 3D printed flow cell 6,34 in which four membranes were tested in four separate cells in parallel. High initial flux conditions (200 LMH) were chosen to significantly accelerate membrane fouling, 39−41 and 24 h fouling runs were performed at constant pressure with secondary treated wastewater.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After this treatment, scanning electron microscopy showed that the membrane surface and pores that were previously covered by the photoinitiator coating became visible again (Figure S3). Membrane performance testing utilized a custom designed 3D printed flow cell 6,34 in which four membranes were tested in four separate cells in parallel. High initial flux conditions (200 LMH) were chosen to significantly accelerate membrane fouling, 39−41 and 24 h fouling runs were performed at constant pressure with secondary treated wastewater.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…29−33 Herein, patterned UV light from a threedimensional (3D) printer with DLP technology was adapted to initiate grafting of polymers onto surfaces of membranes. This stereolithographic technique achieved a striped pattern in three different polymer compositions and was tested in a microfluidic cross-flow cell 6,34 in an orientation perpendicular or parallel to the direction of the inlet water flow. The aqueous feed test solution consisted of secondary treated wastewater, representing a complex mixture of salts, natural organic matter, colloidal material, and microbes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lefebvre et al researched the flow of artificial microcapsules in microfluidic channels for determining the elastic properties of the membrane . Wardrip et al presented a three‐dimensionally printed microfluidic cross‐flow system . Warkiani et al studied the membrane fouling at the microscale using isopore filters .…”
Section: Methods Of Manufacturing Membranes In Microfluidicsmentioning
confidence: 99%
“…32 Wardrip et al presented a three-dimensionally printed microfluidic cross-flow system. 33 Warkiani et al studied the membrane fouling at the microscale using isopore filters. 34 Zhan et al studied the enhanced pervaporation performance of multi-layer pdms/pvdf composite membrane.…”
Section: Methods Of Manufacturing Membranes In Microfluidicsmentioning
confidence: 99%
“…Membrane-facilitated molecular separations play a key role in many large-scale industrial processes, ranging from seawater desalination to fruit juice clarification, and also in milliliter-scale sample processing in biomedical research laboratories (van Reis and Zydney 2007;Saxena et al 2009;Kazemi et al 2016). Miniaturization towards microliter volumes can be achieved by integrating membranes with microfluidic systems (de Jong et al 2006;Chen et al 2016;Roelofs et al 2015;Wardrip and Arnusch 2016;Han and Hwang 2018). Microfluidic chips also enable in situ microscopy of the membrane, e.g., to study membrane fouling, and electrical or optical characterization of the permeate and retentate phases, facilitating separation performance evaluation of novel membrane materials and transport mechanisms (Roelofs et al 2015;Kwak et al 2013;Kornreich et al 2014).…”
Section: Introductionmentioning
confidence: 99%